Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA Menggunakan Metode Eksperimen di Kelas IV SD Negeri 23 Pincuran Tinggi Panyalaian - Diva, Annisa Corie La; zen, Mulyani; Desniati, Desniati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The aim of this research was to describe the improvement of student’s learning outcomes in learning Natural Science by using Experiment method  at 4th grade of Pincuran Tinggi Panyalaian. The subject of this research were the teacher and the students (20 students). The result of this research showed that a) there was  an improvement at the lesson plan design from 85,71%% in cycle I into 94,63% in cycle II, b) in term of teacher’s aspect, the percentage enchanced from 77,5%% in cycle II to 92,5% in cycle II. Meanwhile, in term of the student’s aspect, the percentage increased from 75% in cycle I to 87,5% in cycle II, c) the student’s outcomes improved from 78,2% in cycle I to 87,7% in cycle II.